Timing of Carotid Endarterectomy After Stroke: Retrospective Review of Prospectively Collected National Database. Issue 3 (September 2018) - Tanious, Adam; Pothof, Alexander B.; Boitano, Laura T.; Pendleton, Alaska A.; Wang, Linda J.; de Borst, Gert J.; Rattner, David W.; Schermerhorn, Marc L.; Eslami, Mohammad H.; Malas, Mahmoud B.; Eagleton, Matthew J.; Clouse, William Darrin; et al.
Abstract : Objective: Our objective was to identify the postoperative risk associated with different timing intervals of repair. Background: Timing of carotid intervention in poststroke patients is widely debated with the scales balanced between increased periprocedural risk and recurrent neurologic event. National database reviews show increased risk to patients treated within the first 2 days of a neurologic event compared to those treated after 6 days. Methods: Utilizing Vascular Quality Initiative data, all carotid interventions performed on stroke patients between the years 2012 and 2017 were queried. Patients were then stratified based on the timing of surgery from their stroke (<48 hours, 3–7 days, 8–14 days, >15 days). Major outcomes included postoperative stroke, death, and myocardial infarction. Results: A total of 8404 patients were included being predominantly men (5281, 62.8%), with an average age of 69 (±10). Patients treated at greater than 8 days showed significantly less risk of postoperative combined stroke/death and postoperative stroke. There were no significant differences in postoperative stroke or death between the 8 to 14 and greater than 15 days groups. Multivariate regression analysis showed that delayed timing of surgery between 3 and 7 days was protective for postoperative stroke/death ( P = 0.003) and any postoperative complication ( P = 0.028). Delaying surgery to more than 8 days after stroke was protective for postoperative stroke/death ( P < 0.001), postoperative stroke ( P < 0.001), and any postoperative complication ( P < 0.001). Conclusions: Carotid revascularization should occur no sooner than 48 hours after index stroke event. Surgeons should strive to operate between 8 and 14 days to protect against postoperative stroke/death.